ANSWERING STUDENTS' SOCIAL CHALLENGES: IMPLEMENTING ADAPTIVE AND RESPONSIVE GUIDANCE AND COUNSELING SERVICES - Putri, Annisa Murdanti; Sanjaya, Nur Aeni (PT Altin Riset Publishing, 2025)
The purpose of this study is to determine the implementation, supporting, and inhibiting factors of guidance and counseling services in the personal-social field at SMP Muhammadiyah 2 Banjarmasin. This research method uses a qualitative approach with a descriptive type. The subjects of this study are guidance and counseling teachers, academic teachers, and grade VIII students at SMP Muhammadiyah 2 Banjarmasin. Data collection techniques through observation, interviews, and documentation. The results of this study show that the implementation of personal-social guidance and counseling services at SMP Muhammadiyah 2 Banjarmasin uses classical guidance services, group counseling, and individual counseling. The supporting factors are (1) facilities and infrastructure, (2) support for the principal, and (3) cooperation with academic teachers. The inhibiting factor is that students/counselors do not want to tell the problem to the guidance and counseling teacher.